REGIONAL COOPERATION BETWEEN THE SOUTH CAUCASIAN COUNTRIES AND THEIR ECONOMIC DEVELOPMENT - PANAHOV MAARIF, Azer (Studia Universitatis Babes-Bolyai Studia Europaea, 2017)
The article reviews the issues of the geopolitical priorities in the development of the South Caucasus countries. The article provides a general assessment of the situation in the countries of the region, economic aspects of interaction in the context of extraction, processing and transportation of the energy resources along the energy corridors. Several other aspects of the economic and political relations between Azerbaijan and Georgia, as well as with Armenia, are reviewed as well. The article provides an assessment of the subsequent development of relations in terms of international programs implemented by Germany, the countries of the European Union, as well as by an international bank, and defines their common prospects.